PENGARUH LOVE OF MONEY DAN PERILAKU MACHIAVELLIAN TERHADAP PERSEPSI ETIS INTERNAL AUDITOR BANK PERKREDITAN RAKYAT - Adi Wasita, Putu Aristya; Lasmini, Ni Nengah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
Assessment of conditions or mistakes is called ethical perception. A person who works as an accountant will make high reservations by sticking to existing ethical standards. Competition is tighter, so the accounting profession must often clash with efforts to stick to ethical standards. The internal auditor's view in assessing an improper act will provide a perception of ethical perceptions for the community related to accountability and transparency. This research was conducted to get the influence of the variable love of money, Machiavellian with gender as a moderator on the ethical perceptions of the people's prekreditan bank internal auditors. The data in the study were collected using a questionnaire method, so that the research data were classified as primary data. This study will use 43 samples and will be analyzed using moderated regression analysis. The results of the study, after going through the data analysis of love of money and Machiavellian, have a negative effect on the ethical perception variable of BPR internal auditors. Gender as a moderating variable assesses the influence the love of money variable on the ethical perceptions of BPR internal auditors while for Machiavellian, gender does not know.